Deteksi Anemia dan Edukasi Gizi untuk Mencegah Stunting pada Anak Usia Sekolah - Titih Huriah; Falasifah Ani Yuniarti; Siti Hazariah Binti Abdul Hamid (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2023)
The World Health Organization (WHO) reports that the world population suffering from anaemia is 1.62 billion, with a prevalence in elementary school children of 25.4% or 305 million. Iron nutritional anaemia is still a public health problem, with a majority in children 5 - 12 years old at 29% in Indonesia. The impact of anaemia on elementary school students can cause physical growth and development disorders (stunting). One recommended intervention to prevent stunting in school-age children is early detection of anaemia. The procedure of community service is through several stages; the first stage is coordination and preparation, the second stage is anaemia screening in school-age children by doing haemoglobin checks, and the third stage is nutrition education for students through games. The target is elementary school students in grades 3-5 of SDN Kembangan Bantul Yogyakarta. Community service results showed that of the 36 students who measured haemoglobin levels, 14.5% had anaemia. The results showed before nutrition education, 77,4% of students had less knowledge, and 22,6% had enough knowledge. Meanwhile, 11,3% of students had less knowledge, 56,6% had sufficient knowledge after the intervention, and 32,1% had good knowledge. The different tests showed a p-value of 0.024, meaning an increase in nutritional knowledge after being given nutritional education through games to students of SDN Kembangan Bantul Yogyakarta.